Brugada Pattern Electrocardiogram Unmasked with Cocaine Ingestion - Alraies, M. Chadi (Hindawi Publishing Corporation, 2013)
Cocaine is considered a leading cause of drug-related deaths. This is usually sudden, unwitnessed, and without prodromal features. It has been reported that in-hospital mortality is close to 2%. Cocaine has powerful central nervous system effects(1) and acute cocaine overdose has been associated with hyperthermia, agitation, paranoid ideation, status epilepticus, ventricular fibrillation, ventricular tachycardia, and myocardial infarction (MI). The mechanisms of cocaine-related death remain poorly understood. We report a patient who survived massive cocaine ingestion with psychomotor agitation and generalized seizures followed by asystolic cardiac arrest and transient Brugada pattern on electrocardiogram (ECG).